The effect of the (BOXING SMART GROUND) device in improving some Biokinematic variables and learning the movement of the feet in boxing for students (Journal of Humanities and Social Sciences Research, 2022)
The importance of this study lies by entering into a topic that has an effective role in the use of an auxiliary device in the sports field, as this study invented "The effect of the boxing smart ground in improving some biokinematic variables and learning the movement of the feet in boxing for students" and trying to reach the ideal mechanical performance in the educational process, as finding this device will help to solve a mechanical problem that has a clear and effective impact on boxing effectiveness It is the movement of the feet, it accelerates the learning process as well as this study provides both the elements of suspense, excitement, safety and economy in effort and time in learning other boxing skills and the researcher assumed that the exercises of the boxing smart ground in improving some biokinematic variables and learning the movement of the feet in boxing for students. The researcher used the experimental approach in the manner of the two equivalent groups (control - experimental) with two measurements (pre- and dimensional) After analyzing the statistical data using the statistical bag spss, a development appeared in the movement of the feet and the studied variables and for the control and experimental groups, and the conclusions of the research were shown:- The most important conclusions1- The proposed boxing smart ground has a positive effect in improving some biokinematic variables of the skill of movement of the feet.- The most important recommendations1 - Using the device (boxing smart ground) in the process of teaching beginner boxers the skill of moving feet.